Force vector analysis of ski racing technique using fusion motion capture - Brodie, M.; Walmsley, A.; Page, W. (ISBS - Conference Proceedings Archive (Konstanz), 2007)
In this pilot study Fusion Motion Capture has been used successfully to capture the motion of an athlete through an entire giant slalom alpine ski course. The system allows a comprehensive set of measurements to be collected from each ski run and detailed biomechanical analysis can be extended from a short sequence of turns to an entire run. The results have been used to create a new tool for measuring alpine ski racing technique, based on colour coded Force Vector Analysis, independent of the stylistic constraints often imposed by the coach or athlete. Two ski runs completed by a member of the New Zealand ski team have been compared. The difference between the two run times was around 1%; however Fusion Motion Capture and Force Vector Analysis have been used to pick up the subtle changes in technique between the two runs.